LogMAR and Stereoacuity in Keratoconus Corrected with Spectacles and Rigid Gas-permeable Contact Lenses. Issue 4 (April 2018) - Nilagiri, Vinay Kumar; Metlapally, Sangeetha; Kalaiselvan, Parthasarathi; Schor, Clifton M.; Bharadwaj, Shrikant R.
Abstract : SIGNIFICANCE: This study showed an improvement in three-dimensional depth perception of subjects with bilateral and unilateral keratoconus with rigid gas-permeable (RGP) contact lens wear, relative to spectacles. This novel information will aid clinicians to consider RGP contact lenses as a management modality in keratoconic patients complaining of depth-related difficulties with their spectacles. PURPOSE: The aim of this study was to systematically compare changes in logMAR acuity and stereoacuity from best-corrected spherocylindrical spectacles to RGP contact lenses in bilateral and unilateral keratoconus vis-à-vis age-matched control subjects. METHODS: Monocular and binocular logMAR acuity and random-dot stereoacuity were determined in subjects with bilateral (n = 30; 18 to 24 years) and unilateral (n = 10; 18 to 24 years) keratoconus and 20 control subjects using standard psychophysical protocols. RESULTS: Median (25th to 75th interquartile range) monocular (right eye) and binocular logMAR acuity and stereoacuity improved significantly from spectacles to RGP contact lenses in the bilateral keratoconus cohort ( P < .001). Only monocular logMAR acuity of affected eye and stereoacuity improved from spectacles to RGP contact lenses in the unilateral keratoconus cohort ( P < .001). There was no significant change in the binocular logMAR acuity from spectacles to RGP contact lenses in the unilateral keratoconus cohort. The magnitude of improvement in binocular logMAR acuity and stereoacuity was also greater for the bilateral compared with the unilateral keratoconus cohort. All outcome measures of cases with RGP contact lenses remained poorer than control subjects ( P < .001). CONCLUSIONS: Binocular resolution and stereoacuity improve from spectacles to RGP contact lenses in bilateral keratoconus, whereas only stereoacuity improves from spectacles to RGP contact lenses in unilateral keratoconus. The magnitude of improvement in visual performance is greater for the binocular compared with the unilateral keratoconus cohort.